The importance of Rydberg orbitals in dissociative ionization of small hydrocarbon molecules in intense few-cycle laser pulses. (August 2015) - Jochim, Bethany; Siemering, R; Zohrabi, M; Voznyuk, A; Mahowald, J B; Schmitz, D G; Betsch, K J; Berry, Ben; Severt, T; Kling, Nora G; Burwitz, T G; Ablikim, U; et al.
Synopsis: We demonstrate the importance of ionization from Rydberg orbitals via experimental and theoretical work focusing on the strong-field dissociative single ionization of small hydrocarbons. Our findings suggest that Rydberg states should be routinely considered when studying polyatomic molecules in intense laser fields.